KERAMIK CINA MENGUAK PERADABAN MANUSIA - Noor Sudiyati (Ars: Jurnal Seni Rupa dan Desain, 2009)
Ceramic is a cultural creation that shows human civilization at the moment it   is created. Ceramic is also a reliable reference to reveal the history of a nation, not only from the high quality of its material, but also from the documentation applied on it. Chinese ceramic existed within a period of various dynasties had peculiar feature and specific characteristic. Chinese civilization history is eternally recorded in their   ceramic ornament. Those ceramics contain symbols, hope,narration and artistic expression that words cannot express. Moreover, information of civilization thousands years ago, can be obtained from various motives  and symbols printed on ceramics.Keywords    :    ceramics,    ornament,    civilization